2015
DOI: 10.1021/cn5003489
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin Modulates Developmental Microglia via 5-HT2B Receptors: Potential Implication during Synaptic Refinement of Retinogeniculate Projections

Abstract: Abstract.Maturation of functional neuronal circuits during central nervous system development relies on sophisticated mechanisms. First, axonal and dendritic growth should reach appropriate targets for correct synapse elaboration. Second, pruning and neuronal death are required to eliminate redundant or inappropriate neuronal connections. Serotonin, in addition to its role as a neurotransmitter, actively participates in postnatal establishment and refinement of brain wiring in mammals. Brain resident macrophag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
95
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 96 publications
(103 citation statements)
references
References 43 publications
8
95
0
Order By: Relevance
“…Thus, the current knowledge of the function of Htr2b in microglial cells remains limited to in vitro studies (this study (Fig. 7) or previous results [40]). The generation and characterization of knock-out mice in which Htr2b deletion is restricted to microglia will yield invaluable insights into this question.…”
Section: Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…Thus, the current knowledge of the function of Htr2b in microglial cells remains limited to in vitro studies (this study (Fig. 7) or previous results [40]). The generation and characterization of knock-out mice in which Htr2b deletion is restricted to microglia will yield invaluable insights into this question.…”
Section: Discussionmentioning
confidence: 91%
“…In human peripheral macrophages, 5-HT 2B R mediates the response to serotonin by skewing macrophages to a M2, anti-inflammatory, phenotype [14]. More relevant to ALS, we showed that 5-HT 2B R is the major serotonin receptor expressed on perinatal microglia and regulates chemotaxis of microglial processes in response to serotonin [40]. These findings raise the possibility that the observed 5-HT 2B R upregulation could be linked to microglial activation and function in the pathogenesis of ALS.…”
Section: Introductionmentioning
confidence: 80%
See 3 more Smart Citations